What do you meme? : humor, comunicação, cognição e relevância - Oliveira, Vanessa Cristiane Vanzan de (2020)
This research presents six analysis considering the possible understanding of internet memes on two social medias, through the comments posted by users under the cognitive-pragmatic bias of Sperber & Wilson's Relevance Theory (1996). The linguistic interactions are analyzed, through user comments, and categorized into: i) successful and ii) unsuccessful. We stablish as hypothesis for (i) the possible contribution of humor to the creation of the optimal relevance, and for (ii) the lack of relevance to the processing, onsidering previous knowledge as a possible determinant for that. Memes are a product of digital culture, and therefore many characteristics of this way of communicating can be observed in this modality. Processing may be even more dependent on the addressee’s inferential capacity when one is dealing with humorous genre (GOLDNADEL & OLIVEIRA, 2007; YUS, 2016). The addressee needs to infer and select the best contexts to be accessed. For this reason, we present our analyses highlighting the cognitive processing with some specific definitions that show not only aspects of the Relevance Theory, but also more modern theories, which include the elucidation and transmission of culture, focused on cognitive issues on humor interpretation (SANTOS, 2014; YUS, 2018). We present a way of organizing the interpretative path so that the language users can get the utterances’ meaning, specially, internet meme’s meanings, considering the role of images, which directly affect the deduction and derivation of the assumptions (FORCEVILLE, 2014). We highlight that the relevance of humorous texts, which present little informative value, is generated due to effects (YUS, 2018c) that are beyond the act of communication itself. The results of the analysis indicate that: (i) was partially confirmed, not all humorous memes were optimally processed; and (ii) was confirmed, considering the comments, especially on more context-dependent memes, the internet users did not create the intended inferences. Considering the comments posted on the virtual environment a rich way of researching about pragmatic-cognitive topics on linguistic studies, which is related to humor as well as cultural aspects, we believe that this study contributes to the field by offering significant insights on linguistic interaction found on dynamic corpora.